PENGEMBANGAN MEDIA PEMBELAJARAN LITERASI CERGAM BERBASIS E-BOOK ANDROID TERHADAP MINAT BACA SISWA KELAS III SD - Ahmad Syukri Endiawan; Irfai Fathurohman; Santoso Santoso (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This study to develop literasy of drawing story based on android e-book and find Interest in reading improvement of student learning outcomes on the theme of love plant and animals, sub-one the benefits of plants of human life, exspecially in third-class of elementary school Terangmas Undaan Kudus.The resulting product is form of learning media.The resarch method used use media development with a qualitative approachto the method is Quasi Experimental Design and Nonequivalent Control Group. This research was conducted at Terangmas Elementary School as an exsperimental class and Medini elementary school as an control class.Value research results sig. Levene's Test for Equality of Variances of 0.206. Because the significance is more than 0.05 or can be served 0.206 < 0.05 then it can be concluded that data varians between exsperiment groups and control groups are equally homogeneous.Then based on the table above also known that value sig.(2 tailed) t-test for Equality of Means of 0.000 < 0.005. The results concluded that H0 rejected and Ha received. That means there are significant differences between the average reading interests of exsperiment class and cotrol class.